THE PLACE OF ETHNOTOPONYMS IN TOPONYMY - Usmonova Sofiya Alimovna; Juraeva Ramziya Abdurahimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the ethnotoponyms that take place in the toponyms of the city of Kokand - Yuzlar, Urganji, Gaziaglyk, Kashkaryon, Toglik, Galcha, Avgonbog, Luliyan, Juhutmahalla.